Education and middle-class society in imperial Austria, 1848-1918 - Cohen, Gary B., 1948- (Purdue University Press, 1996)
The development of Austrian society in the nineteenth century was beset by enormous difficulties, including sharp social-class differences, an economic base that was developing all too slowly and unevenly, and, distinct from most of Western and Central Europe, a multiplicity of competing ethnic and religious groups. Against this backdrop, Education and Middle-Class Society in Imperial Austria, 1848-1918 - the first English-language book on the topic - examines Austria's educational system, which Gary B. Cohen characterizes as one of the major accomplishments of government and civil society under the Habsburg Monarchy in its last decades.